Asymetria maksymalnej siLy konczyn dolnych u lekkoatletów - sprinterów róZnego poziomu zaawansowania sportowego - Juszkiewicz, T.; Starosta, W. (Medycyna sportowa, 2001)
When studying the strength status of sprinters, the strength of one leg only or the total of both legs are frequently measured. The aim of this study was to determine the asymmetry of legs, regarding strength, in sprinters (n = 125) differing in age and athletic experience. Maximal isometric strength of individual muscle groups of lower extremities was measured according to B.M. Rybalko. In the process of advancement, asymmetry increased until about reaching the level of sport class II, and decreased with higher advancement. The values of total strength of the right or left legs indicated that in 72% of athletes, the take-off leg was stronger from the other one. In consequence, in over 1 of athletes the swing leg was stronger, i.e. they executed the take-off from the weaker leg. For the swing leg, a more advantageous flexor-to-extensor ratio for the thigh, lower leg and foot were noted. Moreover, higher correlations between those ratio and running time (100 m) were found for that leg.